Research of the self-regulation of human perceptual activity - Ambrazevičius , R. (Psichologija, 1980)
It has been established that the self-regulation of human activities influences the quality of one's work. The aim of the present work is to find out whether the effect mentioned would accompany the fulfilment of perceptual tasks. The conclusion is made that the perceptual activity is influenced by the self-regulation process. It has been shown that the self-control takes part in such kind of mental processes as a mechanism of the compensation.
Keywords: perception; self-regulation of perceptual activity